Assessment of natural groundwater salinization processes in the eastern portion of the Cachoeira River Basin, Bahia - Teramoto, Elias Hideo [UNESP]; Chang, Hung Kiang [UNESP] (Instituto Geologico, 2020)
A substantial portion of Northeastern Brazil undergoes water scarcity, which accounts for important negative local socioeconomic impacts. In addition to water deficit, this region is affected by groundwater salinization, which contributes to the loss of water potability. In the Cachoeira River Basin, located on the eastern border of the State of Bahia semiarid region, high concentrations of naturally dissolved salts are found in groundwater, which result from high rates of evapotranspiration and rock-water interaction. For a quantitative assessment of these processes using total dissolved ion concentrations, multivariate statistics and geochemical simulations were used. Principal Component Analysis revealed that Principal Component 1 (PC1) and 2 (PC2) account for 82.89 and 13.68% of the variance of ion concentrations, respectively. While PC1 is mostly related to variations in HCO3- concentrations, PC2 is mostly related to variations in Cl- concentrations. We also verified that hydrochemical changes define three different trends, highlighting CP2 variations distinct from those observed in CP1, reflecting different proportions of evapotranspiration and rock-water interaction contributions to salinity. Geochemical simulations were able to reproduce ion concentrations in more saline samples from evaporation and rock-water reactions. Most groundwater samples are grouped along Trend 3, whose increase in total dissolved solids is mostly explained by rock-water interactions. Contrarily, the less frequent Trends 1 and 2 are mostly explained by water evaporation.
AvaliaÇÃo de processos naturais de salinizaÇÃo de Águas subterrÂneas na porÇÃo leste da bacia do Rio Cachoeira, Bahia
Keywords: Dissolution of silicates; Geochemical modeling; Rock-water interaction; Salinization